Response of Bird Community to Various Plantation Forests in Gunung Walat, West Java, Indonesia - Aronika Kaban; Ani Mardiastuti; Yeni Aryati Mulyani (HAYATI Journal of Biosciences, 2017)
Different plantation forests possibly harbor different bird communities. This study was aimed to reveal responses of bird community to the different plantation (Schima wallichii, Agathis loranthifolia, Pinus merkusii, and mixed plantation), identify species shared in all plantation, and species confined to a particular plantation. The study site was plantation forests, using the point count method for 64 effective hours. There were 40 bird species (maximum prediction 52) in all forest plantations and each type had 26–31 species. Number of individuals, species density, and diversity index in Schima plantation were higher, followed by Agathis, Pinus, and mixed plantations. Mixed plantation could have harbored more species based on the prediction by Chao. Although there were some differences in tree species, tree sizes, and tree heights, the response of bird composition in all plantations was not differed (93–81% similarity) probably because of the short distances among the forests, the abundance of food insects, and the same late-successional stages. There were 15 (37.5%) widely distributed species in all forest types. Eight species were confined only to a specific forest type. Four species were considered true confined species, namely Javan sunbird (Schima forest), Grey-cheeked bulbul (in Pinus), Crescent-chested babbler (Agathis), and Mountain white-eye (Agathis).